Genes and athletes - Patel, D. R.; Greydanus, D. E. (Adolescent Medicine, 2002)
Genetics plays an important role in determining characteristics desired for success in a given sport. Advances in biotechnology pose interesting and perplexing dilemmas for athletes, parents, health care providers, and society at large. Gene therapy holds great prospects for disease prevention and treatment. The same techniques also can be misused for genetic manipulation to enhance athletic prowess. This chapter reviews selective aspects of genotype influence on sport performance, uses and misuses of genetic technology, and ethical as well as legal dilemmas.